(untitled) (Eurasian Journal of Research, Development and Innovation, 2022)
This article contains recommendations for the sustainable development of the fruit and vegetable industry in the processing and storage of fruit and vegetables in the Republic of Uzbekistan, as well as suggestions for further support of the industry